Analysis of the Effects of Internal and External Factors on Bank Profitability: Comparison of State-Owned Banks and Regional Development Banks (BPD) - ASIFAH, NIRA; KRESNA SAKTI, RACHMAD (Contemporary Studies in Economic, Finance and Banking, 2025)
This study aims to determine the effect of several internal variables (NPL, LDR, & Operation Cost Ratio to Operating Income) and external variables (GDP/GRDP) on the profitability of state-owned banks (BUMN) and Regional Development Bank (BPD) by looking at the ROA value for the period 2011 - 2020. In addition to looking at the effect of these independent variables, a comparison of the two government-owned banks was also carried out. The analysis method used is panel data model regression analysis. The approach used in this study is a type of associative and comparative quantitative approach. This study is compiled based on data in the form of figures from the financial statements of state-owned banks (BUMN) and Regional Development Banks (BPD), so that it is said to be quantitative research. This study shows that the independent variables have different effects on profitability (ROA) between state-owned banks (BUMN) and Regional Development Banks (BPD). This difference is because the two types of banks have different characteristics, including the amount of asset value owned and market reach or operational area which will affect customer diversity.